AN ANALYSIS OF IDEATIONAL IN THE SPEECH OF LAUREN SINGER - Sarah Nasrani Gea; Srisofian Sianturi; Dewi Paulina Silalahi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the ideational analysis of Lauren Singer’s speech using Systemic Functional Linguistics (SFL) theory as proposed by Halliday and Matthiessen (2014). The objectives of this study are to identify the types of ideational processes found in Lauren Singer’s speech, determine the most dominant ideational process, and describe the reasons why this dominant process appears more frequently in the speech. This study employs a qualitative descriptive research method. The research data were obtained from sentences that had been broken down into clauses discussing a zero-waste lifestyle. The results indicate that there are six types of processes, with a total of 373 instances found in Lauren Singer’s speech. The most dominant process is the material process, comprising 179 clauses (48.0%), indicating that the speech frequently describes concrete actions or activities. This was followed by relational processes, comprising 115 clauses (30.8%), and mental processes, comprising 67 clauses (18.0%). Meanwhile, verbal processes were found in 8 clauses (2.1%), while behavioral and existential processes were each found in 2 clauses (0.5%). An analysis of Lauren Singer’s speech shows that the material process is the dominant process, indicating that the speaker emphasizes actions the audience can take to adopt a zero-waste lifestyle. The purpose of this is to provide insight and encourage the audience to change their behavior in daily life in order to reduce waste and protect the environment. The reasons why the material process is the dominant process are as follows: first, this speech focuses on concrete actions; second, the purpose of this speech is to persuade or influence; third, this speech is supported by quantitative data